PENGARUH KEPEMIMPINAN, KEPRIBADIAN, UMUR, DAN PENDIDIKAN TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI PEGAWAI BALAI PELAKSANA TEKNIS BINA MARGA WILAYAH TEGAL - Mr. Wasmo; Mr. Basuki (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2017)
The purpose of this research is 1) to describe leadership, personality, age, education, motivation and the employee performance 2) to know the influence of leadership, personality, age, and education motivation employees to 3) to know the influence of leadership, personality, age, and education against the employee performance 4) to know the motivation to performance employees and 5) to know the influence of leadership, personality, age, and education on performance through motivation. Respondents in this study by the 107. These respondents are civil of technical execution Bina Marga Region Tegal. The methods of this research use Structural Equation Modeling (SEM) who run through AMOS as a means of the analysis. Is the between leadership, personality, age and education for employees at the motivation bina marga the tegal. This is evidenced of the value of the terstandar regression (beta) leadership motivation to obtain value of 0,11, to obtain personality motivation value of 0,32, my motivation to obtain value of -0,19 and education motivation to obtain value of 0,23 and more tender testing obtained value p-value very small (< 0,001). There are relations between leadership, personality, age and education of the performance of employees in city bina marga areas tegal. This is evidenced of the value of the regression coefficient terstandar (beta) leadership of the performance of have value of 0,06, personality of the performance of have value of 0,48, age of the performance of get value 0.01 and education on performance have value of 0.09 and from the testing obtained value pvalue very small (< 0,001). the incentives on performance in city bina marga areas tegal. This is evidenced of the value of the regression coefficient terstandar (beta) motivation on performance have value of 0,36 and from the testing obtained value pvalue very small (& lt; 0,001). Is the between leadership, personality, age and education on performance through motivation in city bina marga areas tegal. This is evidenced value the regression coefficient terstandar (beta) leadership, personality, of and education on performance through motivation have value of. 30 and from the testing obtained value p-value very small (< 0,001). There are relations between leadership, personality, age and education through motivation to performance in the region tegal bina marga.This is evidenced value regression coefficient terstandar (beta) leadership, personality, age) and education on performance through motivation for value of 0,30 and more tender testing obtained value p-value very small (< 0,001). Keywords: leadership, personality, age, education, motivation and performance.